2023
DOI: 10.1002/jcsm.13321
|View full text |Cite
|
Sign up to set email alerts
|

Physical function endpoints in cancer cachexia clinical trials: Systematic Review 1 of the cachexia endpoints series

James McDonald,
Judith Sayers,
Stefan D. Anker
et al.

Abstract: In cancer cachexia trials, measures of physical function are commonly used as endpoints. For drug trials to obtain regulatory approval, efficacy in physical function endpoints may be needed alongside other measures. However, it is not clear which physical function endpoints should be used. The aim of this systematic review was to assess the frequency and diversity of physical function endpoints in cancer cachexia trials. Following a comprehensive electronic literature search of MEDLINE, Embase and Cochrane (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 101 publications
1
8
0
1
Order By: Relevance
“…Resistance training (RT), as a measure to reduce or even reverse muscle wasting, is recommended in addition to endurance training to improve CRF by current guidelines of sports cardiology and cardio-oncology [ 8 , 94 ] as it improves skeletal muscle and mitochondrial respiration [ 95 ]. Assessment of muscle strength in cancer patients is usually performed by measuring handgrip strength [ 96 ], and RT intensity to establish training prescriptions should be identified by the one repetition maximum (1 RPM) [ 89 , 94 ]. A meta-analysis of randomized trials of RT during and after chemotherapy in cancer survivors demonstrated the most effective increase of muscle strength at intensities below 75% of 1 RPM [ 97 ] and provides evidence for a safe integration of RT into training of cancer patients.…”
Section: Exercise Interventions In Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance training (RT), as a measure to reduce or even reverse muscle wasting, is recommended in addition to endurance training to improve CRF by current guidelines of sports cardiology and cardio-oncology [ 8 , 94 ] as it improves skeletal muscle and mitochondrial respiration [ 95 ]. Assessment of muscle strength in cancer patients is usually performed by measuring handgrip strength [ 96 ], and RT intensity to establish training prescriptions should be identified by the one repetition maximum (1 RPM) [ 89 , 94 ]. A meta-analysis of randomized trials of RT during and after chemotherapy in cancer survivors demonstrated the most effective increase of muscle strength at intensities below 75% of 1 RPM [ 97 ] and provides evidence for a safe integration of RT into training of cancer patients.…”
Section: Exercise Interventions In Cancer Patientsmentioning
confidence: 99%
“…Recent trials used combined AET and RT to demonstrate improvement of CRF in patients during and after chemotherapy [ 50 •, 65 •, 98 ], but did not include frail and sarcopenic patients [ 96 , 99 ]. Future exercise studies in cancer patients need to take this into account and should also enroll sarcopenic cancer patients who should be trained with combined RT and AET and additional structured nutritional advice.…”
Section: Exercise Interventions In Cancer Patientsmentioning
confidence: 99%
“…Des progrès dans ces domaines permettraient à la fois d'intervenir à des stades de pré-cachexie, où les symptômes pourraient être encore réversibles, et de personnaliser l'approche thérapeutique de cette maladie très hétérogène. L'amélioration du diagnostic permettrait aussi de mieux définir les critères d'efficacité proposés dans les protocoles d'essais cliniques, souvent remis en question par les agences réglementaires [27] . Il est désormais admis que la prise en charge de la cachexie devrait être multimodale, associant, en combinaison, des thérapies ciblées anaboliques, anticataboliques et anti-inflammatoires, des approches nutritionnelles et pharmacologiques de l'anorexie, et des protocoles d'exercice physique visant à contenir la perte musculaire [28].…”
Section: La Thérapie Anti-cachexieunclassified
“…CAS is a complex multifactorial syndrome with ongoing skeletal muscle loss despite nutritional intervention, and the patient may or may not present with fat mass loss [3]. It is a significant clinical finding of great importance because the presence of cachexia is associated with shorter survival [4][5][6], poor physical functioning [7], reduced response to chemotherapy, and a negative impact on the quality of life [8]. Refractory cachexia in advanced non-curable cancer patients has a prognosis of less than 3 months [9].…”
Section: Introductionmentioning
confidence: 99%